An in vitro model to mimic the thrombotic occlusion of small vessels in catastrophic antiphospholipid syndrome (CAPS). (December 2019) - Pontara, E; Cheng, C; Cattini, M G; Bison, E; Pelloso, M; Denas, G; Pengo, V
Platelet activation and decrease in platelet count characterize the development of the most feared form of antiphospholipid syndrome (APS), i.e. catastrophic APS (CAPS). We aimed to assess if immuno-affinity purified anti-β2-glycoprotein I (aβ2GPI) antibodies enhance platelet activation inducing a significant flow obstruction in a platelet function analyzer (PFA). Affinity purified aβ2GPI antibodies were obtained from 13 triple positive patients with a strong lupus anticoagulant (LA) and high titers of IgG anticardiolipin antibodies (aCL) and IgG aβ2GPI. Platelet activation stimulated by adenosine diphosphate (ADP) in the presence or absence of aβ2GPI was measured by the expression of P-selectin on platelet surface using flow cytometry. P-selectin expression remained close to baseline when normal whole blood was incubated with aβ2GPI alone. When stimulated using aβ2GPI combined with ADP, P-selectin expression (28.42 ± 5.15% vs. 20.98 ± 3.94%, p  = 0.0076) was significantly higher than ADP alone. Closure time of normal whole blood passed through the PFA was significantly shorter using affinity purified aβ2GPI than control IgG both in Col/ADP (160.1 ± 62.1 s vs. 218.6 ± 43.8 s; p  = 0.021) and Col/EPI cartridges (149.5 ± 26.7 s vs. 186.9 ± 45.5 s; p  = 0.030). Thus, platelet activation is enhanced by aβ2GPI antibodies with a consequent premature closure in a PFA, possibly resembling that in microcirculation in patients with CAPS.